2018
DOI: 10.1266/ggs.17-00028
|View full text |Cite
|
Sign up to set email alerts
|

The scallop IGF2 mRNA-binding protein gene <i>PyIMP</i> and association of a synonymous mutation with growth traits

Abstract: Insulin-like growth factor 2 mRNA-binding proteins (IMPs) function in localization, stability and translational control of their target RNAs. In this study, we identified an IMP gene (PyIMP) from Yesso scallop, Patinopecten yessoensis. The complete DNA sequence of PyIMP was 22,875 bp, consisting of seventeen exons and sixteen introns. The full-length cDNA sequence was 3,293 bp, with an open reading frame of 1,776 bp, encoding 592 amino acids. PyIMP exhibited characters typical of IMPs, namely two RNA recogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Increasing evidence has shown that some SNPs are associated with growth, disease resistance, and other economic traits of clams ( He et al, 2012 ; Siva et al, 2012 , 2016 ; Nie et al, 2015 ; Niu et al, 2015 ; Yao et al, 2020 ; Zhao et al, 2020 ). For instance, a synonymous mutation SNP c.852A > G of insulin-like growth factor 2 mRNA-binding protein gene in Patinopecten yessoensis showed a significant association with the growth traits ( Ning et al, 2018 ), while two SNPs HbIIA-E2-146 and HbIIB-E2-23 of the hemoglobin gene ( Hb ) in Tegillarca granosa were associated with the Vibrio parahaemolyticus resistance ( Bao et al, 2013 ). The +2248T/C and +2365T/C of interferon regulatory factor 2 ( IRF -2) gene in freshwater mussel Hyriopsis cumingii were significantly related to Aeromonas hydrophila resistance ( Wang et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has shown that some SNPs are associated with growth, disease resistance, and other economic traits of clams ( He et al, 2012 ; Siva et al, 2012 , 2016 ; Nie et al, 2015 ; Niu et al, 2015 ; Yao et al, 2020 ; Zhao et al, 2020 ). For instance, a synonymous mutation SNP c.852A > G of insulin-like growth factor 2 mRNA-binding protein gene in Patinopecten yessoensis showed a significant association with the growth traits ( Ning et al, 2018 ), while two SNPs HbIIA-E2-146 and HbIIB-E2-23 of the hemoglobin gene ( Hb ) in Tegillarca granosa were associated with the Vibrio parahaemolyticus resistance ( Bao et al, 2013 ). The +2248T/C and +2365T/C of interferon regulatory factor 2 ( IRF -2) gene in freshwater mussel Hyriopsis cumingii were significantly related to Aeromonas hydrophila resistance ( Wang et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The bay scallop Argopecten irradians is a commercially important bivalve widely cultured in northern China ( Ning et al, 2018 ). The cultured population of the bay scallops originated from only a small number of brood stocks survived from the last attempt of 3 consecutive introductions in early 1980s ( Zhang et al, 1986 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, insulin/ insulin‐like growth factor (IGF) homologues, molluscan insulin‐like peptides (MIPs), and related regulation systems were identified from mollusc species. The identified endocrine system was considered to significantly influence body growth and regulate cell proliferation, cell activity, and glycogen metabolism (Choi et al, 2018; Ning et al, 2018; Zhang & He, 2020). The insulin/IGF pathway exerts its GTP‐dependent stimulation on the adenylyl cyclase activity by activating the mitogen‐activated protein kinase (MAPK) and phosphatidylinositol 3‐kinase (PI3K) pathways.…”
Section: Introductionmentioning
confidence: 99%